2021
DOI: 10.1186/s40643-021-00462-7
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase@HKUST-1: a super stable biocatalyst efficient for catecholic product synthesis

Abstract: Although metal–organic frameworks (MOFs) have been considered as promising matrices for enzyme immobilization, HKUST-1, constructed from copper acetate (CuAc2) and benzene 1,3,5-tricarboxylate (BTC), has rarely been explored for this application. In this study, mushroom tyrosinase (EC 1.14.18.1) was immobilized in the form of tyrosinase@HKUST-1 following a simple reaction procedure by mixing BTC with the enzyme prior to addition of CuAc2. The resultant biocatalyst was characterized in both structural features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This served as a biocatalyst for regioselective ortho-hydroxylation reactions to produce catecholic products with huge pharmacological effects, i.e., hydroxytyrosol and L-DOPA, with excellent yields and productivities and stability. 176 Other recent studies in this section have been documented by Huang et al 177 5.2.3 Photocatalysts. A photocatalyst is a material which absorbs light to bring it to a higher energy level and provides such energy to a reacting substance to make a chemical reaction occur.…”
Section: Catalysismentioning
confidence: 70%
See 1 more Smart Citation
“…This served as a biocatalyst for regioselective ortho-hydroxylation reactions to produce catecholic products with huge pharmacological effects, i.e., hydroxytyrosol and L-DOPA, with excellent yields and productivities and stability. 176 Other recent studies in this section have been documented by Huang et al 177 5.2.3 Photocatalysts. A photocatalyst is a material which absorbs light to bring it to a higher energy level and provides such energy to a reacting substance to make a chemical reaction occur.…”
Section: Catalysismentioning
confidence: 70%
“…, hydroxytyrosol and l -DOPA, with excellent yields and productivities and stability. 176 Other recent studies in this section have been documented by Huang et al 177…”
Section: Trends In the Application Of Metal Organic Frameworkmentioning
confidence: 72%
“…Tyrosinase is another copper-containing oxidoreductase capable of utilizing atmospheric oxygen as an oxidant, enabling the biocatalytic oxidation of harmful pollutants without the addition of other reagents. Yang’s group encapsulated mushroom tyrosinase into ZIF-8 and HKUST-1 using an in situ encapsulation method. The tyrosinase hybrid biocatalyst demonstrated excellent tolerance to variations in pH and temperature, efficiently removing typical phenolic pollutants and bisphenols in complex environments.…”
Section: Environmental Remediation By Diverse Catalysis Principles Us...mentioning
confidence: 99%
“…For example, Patil et al ( 2021 ) reported that the main metabolite arising from chloropyrifos biotransformation in Trametes hirsuta MTCC-1171 is 2,4-bis (1,1 dimethylethyl) phenol, which is an important fuel additive. Lu et al ( 2021 ) demonstrated that mushroom tyrosinase immobilised in a metal-organic framework (MOF) was a much-improved biocatalyst compared with the non-immobilised enzyme for production of the pharmacologically important catechols L-DOPA and hydroxytyrosol.…”
Section: Pesticidesmentioning
confidence: 99%